1990
DOI: 10.1093/ajcn/52.4.661
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of three cereal brans on plasma lipids, blood pressure, and glucose metabolism in mildly hypercholestece:rolemic men

Abstract: Dietary fiber lowers atherogenic serum lipids and blood pressure and improves glucose metabolism. We compared in 24 mildly hypercholesterolemic men the effects of adding 11.8 g dietary fiber/d from each of three cereal brans (wheat, rice, and oat) to a low-fiber diet for 4 wk each. A double-blind, crossover design incorporated brans into bread and muffins. Plasma total- and low-density-lipoprotein-cholesterol concentrations were significantly lowered only by oat bran. Compared with wheat bran, the ratios of pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
1
2

Year Published

1991
1991
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(77 citation statements)
references
References 17 publications
5
68
1
2
Order By: Relevance
“…/3-Glucan is probably the active portion of the WSDF of oats, but its content is often not given in the publication, a major flaw that has led to a great number of conflicting results. The reduction in TC of about 6% found in this study for the OFS is similar to the reduction of about 5% obtained by Kestin et al, 9 who fed an oat bran supplying 11.8 g/day DF, of which about 50% was WSDF. Van Horn et al 10 also obtained a reduction in mildly hypocholesterolemic subjects of about 5% in 6 weeks with 60 g/day of oat products, and Gold and Davidson, 11 feeding their subjects oat muffins containing about 10 g/day total DF, induced the same 5% reduction in normocholesterolemic subjects.…”
Section: Resultssupporting
confidence: 91%
“…/3-Glucan is probably the active portion of the WSDF of oats, but its content is often not given in the publication, a major flaw that has led to a great number of conflicting results. The reduction in TC of about 6% found in this study for the OFS is similar to the reduction of about 5% obtained by Kestin et al, 9 who fed an oat bran supplying 11.8 g/day DF, of which about 50% was WSDF. Van Horn et al 10 also obtained a reduction in mildly hypocholesterolemic subjects of about 5% in 6 weeks with 60 g/day of oat products, and Gold and Davidson, 11 feeding their subjects oat muffins containing about 10 g/day total DF, induced the same 5% reduction in normocholesterolemic subjects.…”
Section: Resultssupporting
confidence: 91%
“…In the earlier trials with wheat fibre only total cholesterol was measured, not lipoprotein fractions. However in most papers that do report HDLcholesterol it has not been changed significantly by wheat fibre (McDougall et al, 1978;Dixon, 1978;Stasse-Wolthuis et al, 1979;Flanagan et al, 1980;Gariot et al, 1986;Kestin et al, 1990) and wheat fibre has no consistent effect on fasting plasma triglycerides (Truswell & Kay, 1976).…”
Section: (B) Experiments On Effects Of Cereal Foods or Fractions On Rmentioning
confidence: 99%
“…Sixty g=day of rice bran reduced LDLcholesterol slightly, increased HDL-cholesterol slightly, increased the total cholesterol=HDL-cholesterol ratio significantly and lowered triglycerides (Kestin et al, 1990). Fifteen and 30 g=day rice bran reduced plasma triglycerides but not other lipids (Sanders & Reddy, 1991).…”
Section: (B) Experiments On Effects Of Cereal Foods or Fractions On Rmentioning
confidence: 99%
“…Several studies have shown that soluble dietary ®bres, for example plant gums (Anderson, 1985;Jenkins et al, 1979;Miettinen, 1987;Todd et al, 1990;Tuomilehto et al, 1988;Uusitupa et al, 1989) and oat bran Davidson et al, 1991;DemarkWahnefried et al, 1990;DeGroot et al, 1963;Van Horn et al, 1986;Van Horn et al, 1991;Judd & Truswell, 1981;Kestin et al, 1990;Kirby et al, 1981) lower serum total and LDL-cholesterol levels. The main soluble ®bre portion of oat bran is beta-glucan (A Ê hman et al, 1987).…”
Section: Introductionmentioning
confidence: 99%